Analisis Kualitas dan Kuantitas Air Tanah Olele untuk Mendukung Pengembangan Geowisata dan Konservasi Lingkungan - Ninasafitri, Ninasafitri; Pakaya, Ariyanto; Djibran, Fahira Ramadhani; Paladan, Reynhard Batara; Paladan, Rayhand Batara; Pambudi, Moch. Rio (-, 2024)
Groundwater is one of the most important natural resources for human life and ecosystems. This research analyzes the quality and quantity of groundwater in Olele Village, Kabila Bone District, Gorontalo, to support the development of geotourism and environmental conservation. The hydrogeological analysis involved field data collection, physical and chemical measurements of groundwater, and mapping using GIS. Results show that groundwater in Olele is influenced by local geological conditions, such as limestone and proximity to the sea, which causes the water to be classified as brackish. Values of pH, temperature and electrical conductivity are still in accordance with the standard, but TDS exceeds the quality standard limit. Groundwater flow patterns move from high elevations towards the sea, potentially triggering seawater intrusion. This study recommends data-based management to maintain a balance between tourism development and sustainable preservation of groundwater resources.